Alat Peraga Hukum Pascal Untuk Pembelajaran Fisika SMA - Andi Reski; Mitra Rahayu; Retno Dwi Lestari (Musamus Journal of Science Education, 2022)
his study aims to develop Pascal's law teaching aids that are suitable for high school physics learning. This type of research is R&D research and uses a 4-D development model. The product feasibility test is carried out by validating two experts. The research instrument used was a questionnaire validation sheet and data interpretation using the Ideal Standards (SBI). The results showed that the average score of the feasibility test by the validator was 89 in the "Good" category. Therefore, Pascal's law teaching aids that have been developed have been tested worthy of being tested in learning.